High-repetition-rate strong-field terahertz source by optical rectification in DSTMS crystals - Zhuorui Zheng; Kang Wang; Hongyang Li; Xianze Meng; Ye Tian; Liwei Song (High Power Laser Science and Engineering)
We present the generation of high-repetition-rate strong-field terahertz (THz) pulses from a thin 4-N,N-dimethylamino-4’-N’-methyl-stilbazolium 2,4,6-trimethylbenzenesulfonate (DSTMS) organic crystal pumped by an ytterbium-doped yttrium aluminum garnet laser. The generated THz pulse energy reaches 932.8 nJ at 1 kHz repetition rate, with a conversion efficiency of 0.19% and a peak electric field of 819 kV/cm. At a repetition rate of 10 kHz, it is able to maintain a peak electric field of 236 kV/cm and an average THz power of 0.77 mW. The high-repetition-rate, strong-field THz source provides a convenient tool for the study of THz matter manipulation and THz spectroscopy.